The legacy of scholasticism in economic thought: antecedents of choice and power - Langholm, Odd (Historical perspectives on modern economics, 1998)
This book studies the development of ideas on freedom, coercion and power in the history of economic thought. It focuses on the exchange of goods and services and on terms of exchange (interest rates, prices and wages) and examines the nature of choice, that is, the state of the will of economic actors making exchange decisions. In a social context, anyone's range of choice is restricted by the choices made by others. The first to raise the question of the will in this economic context were the medieval scholastics, drawing on non-economic analytic models inherited from antiquity and mainly from Aristotle. From these origins, views on economic choice, coercion and power are recorded, as they gradually change over the centuries, until they manifest themselves in more contemporary disputes between different branches of institutional economics